Hesitancy in the time of coronavirus: Temporal, spatial, and sociodemographic variations in COVID-19 vaccine hesitancy - Ran Liu; Gabriel Miao Li (Elsevier, 2021)
Leveraging nationally representative survey data on 443,680 respondents from January to March 2021, this study examines the temporal, spatial, and sociodemographic variations in COVID-19 vaccine hesitancy in the U.S. Findings reveal multidimensional determinants of vaccination intentions involving confidence, complacency, and circumspection factors. Using descriptive analyses and multilevel mixed-effects regression models, we find persistent partisan divide across states and significant racial disparities, with Blacks more likely to develop vaccine hesitancy due to confidence and circumspection than Whites. Vaccine hesitancy among Blacks declines dramatically across time but varies little across states, indicating new directions to effectively address inequalities in vaccination. Results also show nuanced gender differences, with women more likely to develop hesitancy due to circumspection and men more likely to have hesitancy due to complacency. Moreover, we find important intersection between race, gender, and education that calls for efforts to adequately address the concerns of the most vulnerable and disadvantaged groups.